2009
DOI: 10.1038/bmt.2009.303
|View full text |Cite
|
Sign up to set email alerts
|

Effect of missing killer-immunoglobulin-like receptor ligand in recipients undergoing HLA full matched, non-T-depleted sibling donor transplantation: a single institution experience of 151 Asian patients

Abstract: This retrospective analysis studied the impact of natural killer (NK) alloreactivity based on the missing ligand model, for a cohort of recipients undergoing haemopoietic stem cell transplant without T-cell depletion from HLA full-matched sibling donors. All patients received a uniform myeloablative conditioning regimen and prophylaxis for GVHD. A total of 151 patients were studied, including 62 patients with AML or myelodysplastic syndrome, 42 patients with ALL and 47 patients with CML. We found that 81% of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…In fact, those studies favoring the missing KIR ligand model were largely based on BMT and/or T cell-depleted HSCT. 3,5,[16][17][18]25 On the contrary, most of the studies questioning the missing KIR ligand model were based on combined analyses of BMT and PBSCT, 12,14,20 or were restricted to PBSCT. 21 As an exception, Gagne et al, 22 have reported poor outcome in C2/2 recipients with myelogenous diseases following BMT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, those studies favoring the missing KIR ligand model were largely based on BMT and/or T cell-depleted HSCT. 3,5,[16][17][18]25 On the contrary, most of the studies questioning the missing KIR ligand model were based on combined analyses of BMT and PBSCT, 12,14,20 or were restricted to PBSCT. 21 As an exception, Gagne et al, 22 have reported poor outcome in C2/2 recipients with myelogenous diseases following BMT.…”
Section: Discussionmentioning
confidence: 99%
“…19 Furthermore, a number of clinical studies aimed at reproducing the model have yielded seemingly conflicting results. 3,5,[12][13][14][15][16][17][18][19][20][21]25 So far, the missing KIR ligand model has therefore been considered at best to be of predictive value without suggesting practical consequence, as it relies on the recipient's HLA type, which is evidently irrevocable. Contrasting with this consideration, the present study suggests that a significant advantage might be taken from the differential effects of missing KIR ligands in BMT vs PBSCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since KIR and HLA are inherited independently on chromosome 19 and chromosome 6, respectively [8], an individual may lack one or more HLA epitopes for their inhibitory KIR genes; such individuals are referred to as having a “KIR-ligand missing” genotype. This KIR/KIR-ligand genotype is present in more than 60% of the population [18,6]. Alternatively, those individuals that have HLA epitopes for all of their inherited inhibitory KIR genes are referred to as having “all KIR-ligands present”.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a number of supportive studies for the role of KIR genotypes in HSCT, there are contradicting studies that report negative or controversial association (6,(18)(19)(20)(21). Particularly, there are only a few studies with limited sample size on the effect of KIR genotype in HLA-identical sibling HSCT in Asian population of which use non-T depleted protocols (12,17,20,(22)(23)(24). As the KIR-HLA class I relationship between recipient and donor might become an additional part of the donor evaluation and selection process, more samples and data analysis should be included to reach the conclusion of the usefulness of this additional promising KIR genotyping.…”
Section: Introductionmentioning
confidence: 99%